Strategi Peningkatan Kesuburan Lahan Melalui Optimalisasi Pupuk Organik Untuk Meningkatkan Produktivitas Tanaman Indigofera zollingeriana Skala Lapang: Strategy to Improve Land Fertility Through Optimization of Organic Fertilizer to Improve Productivity of Indigofera zollingeriana Plant on Field Scale (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
This study aimed to evaluate the effect of manure on the production and nutrients of Indigofera zollingeriana legumes on a field scale. This study used a completely randomized design (CRD) with 6 treatments (FS0 = 0 ton ha-1 manure, FS5 = 5 ton ha-1 manure, FS10 = 10 ton ha-1 manure, FS15 = 15 ton ha-1 manure, FS20 = 20 ton ha-1 manure, FS25 = 25 ton ha-1 manure) and 5 replications. The data obtained were tested using analysis of variance (ANOVA) and if there was a significant difference, it was continued with the Duncan test. The results showed that the use of manure effectively increased (p